2013
DOI: 10.1371/journal.pntd.0002396
|View full text |Cite
|
Sign up to set email alerts
|

Adhesins of Leptospira interrogans Mediate the Interaction to Fibrinogen and Inhibit Fibrin Clot Formation In Vitro

Abstract: We report in this work that Leptospira strains, virulent L. interrogans serovar Copenhageni, attenuated L. interrogans serovar Copenhageni and saprophytic L. biflexa serovar Patoc are capable of binding fibrinogen (Fg). The interaction of leptospires with Fg inhibits thrombin- induced fibrin clot formation that may affect the haemostatic equilibrium. Additionally, we show that plasminogen (PLG)/plasmin (PLA) generation on the surface of Leptospira causes degradation of human Fg. The data suggest that PLA-coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 59 publications
1
41
1
13
Order By: Relevance
“…In vitro, Leptospira-bound plasmin degrades ECM components such as fibronectin (Vieira et al 2009) and human fibrinogen , and may activate host matrix metalloproteases which in turn could contribute to tissue degradation. Plasmin-coated leptospires also crossed human umbilical vein epithelial cell monolayers more efficiently than normal leptospires, although the precise mechanism was not investigated (Vieira et al 2013). Taken together these data suggest that surface-bound plasmin may facilitate crossing of ECM and tissue barriers and degradation of fibrin clots by leptospires, resulting in dissemination throughout the host.…”
Section: Leptospiral Binding Of Plasminogenmentioning
confidence: 94%
See 2 more Smart Citations
“…In vitro, Leptospira-bound plasmin degrades ECM components such as fibronectin (Vieira et al 2009) and human fibrinogen , and may activate host matrix metalloproteases which in turn could contribute to tissue degradation. Plasmin-coated leptospires also crossed human umbilical vein epithelial cell monolayers more efficiently than normal leptospires, although the precise mechanism was not investigated (Vieira et al 2013). Taken together these data suggest that surface-bound plasmin may facilitate crossing of ECM and tissue barriers and degradation of fibrin clots by leptospires, resulting in dissemination throughout the host.…”
Section: Leptospiral Binding Of Plasminogenmentioning
confidence: 94%
“…Plasmin-coated leptospires also crossed human umbilical vein epithelial cell monolayers more efficiently than normal leptospires, although the precise mechanism was not investigated (Vieira et al 2013). As found in other pathogens (Lähteenmäki et al 2001), leptospires may up regulate activators of plasminogen in host cells (Vieira et al 2013). As found in other pathogens (Lähteenmäki et al 2001), leptospires may up regulate activators of plasminogen in host cells (Vieira et al 2013).…”
Section: Leptospiral Binding Of Plasminogenmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that leptospires bind human fibrinogen (Oliveira et al, 2013) and human thrombin (Fernandes et al, 2015), reducing fibrin clot formation and possibly interfering with the rheological properties of the clot, a characteristic that might add to the haemorrhagic symptoms in severe leptospirosis. Vieira et al (2009) have reported that pathogenic leptospires are able to bind plasminogen (PLG) and subvert the host machinery to convert it into its active form, plasmin (PLA), the main fibrinolytic enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Vieira et al (2009) have reported that pathogenic leptospires are able to bind plasminogen (PLG) and subvert the host machinery to convert it into its active form, plasmin (PLA), the main fibrinolytic enzyme. PLA-bound leptospires are able to degrade fibrinogen (Oliveira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%